Karakteristik Kemiskinan Di Provinsi Papua Barat Setelah Otonomi Khusus - Sarce Babra Awom (JFRES Journal of Fiscal and Regional Economy Studies, 2021)
This study aims to analyze spending and the characteristics of the poverty level in the province of West Papua and whether the special autonomy fund spending has an effect on fluctuations in levels of poverty in the province of West Papua from 2009-2019 after special autonomy. The method used in this research is quantitative and descriptive. The analysis technique uses secondary data and uses simple regression analysis. From the result of simple regression analysis with the help of the application program, the test results both simultaneously and partially show that the significance value (0,000) is smaller than the sensitivity degree value of 0,05 (5%) so it can be concluded that in a time series, spending on special autonomy funds has an effect on significant fluctuations in poverty levels in the province of West Papua, but not all of them because R2 (R Square) only 67% were 33% influenced by the village fund assistance program, but not measured in this study.